1998
DOI: 10.1097/00002060-199807000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Strength of Trunk Flexion-Extension in Post-Stroke Hemiplegic Patients1

Abstract: This study was undertaken to determine muscle strength of trunk flexion-extension in hemiplegic patients after stroke compared with that of normal controls. The design consisted of a nonrandomized control trial in a secondary care setting (a rehabilitation unit at a hospital facility). The subjects included 25 post-stroke male hemiplegic patients and 25 male healthy controls. The maximal peak torques of trunk flexion-extension at angular velocities of 0 degrees (isometric contraction), 60 degrees, 120 degrees,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 12 publications
2
59
0
3
Order By: Relevance
“…Moreover, increased postural sway worsens these balance difficulties [9]. Previous cross-sectional studies of sitting balance suggest a reduced voluntary bilateral trunk performance in stroke patients [10,11]. Furthermore, voluntary and involuntary muscle activations are impaired predominantly on the paretic side [12,13], resulting in high rates of post-rehabilitation wheelchair dependence [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, increased postural sway worsens these balance difficulties [9]. Previous cross-sectional studies of sitting balance suggest a reduced voluntary bilateral trunk performance in stroke patients [10,11]. Furthermore, voluntary and involuntary muscle activations are impaired predominantly on the paretic side [12,13], resulting in high rates of post-rehabilitation wheelchair dependence [14].…”
Section: Introductionmentioning
confidence: 99%
“…Stroke patients have decreased trunk control ability in all planes, more so in the frontal plane (Rode et al 1997;de Haart et al 2004). Studies reported that stroke patients have decreased trunk muscle strength compared to healthy controls (Tanaka et al 1997(Tanaka et al , 1998, and that chronic stroke patients have a greater reposition error than healthy participants when their trunk proprioception was measured (Ryerson et al 2008). For these reasons stroke patients have decreased weight-shift ability (Mudie et al 2002) and trunk control (Verheyden et al 2005) and therefore weightshifting and balance are considered fundamental for functional activities (Howe et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…AsM5 is located within the anterior parts of the MCA territory which is hypothesized to represent sensory and motor areas of the cortex, the right M5 location could be hypothesized to have a greater role in the regulation of trunk control than left.Early information about lesion location together with assessment of trunk control may help guide therapists in their treatment choices and emphasis in intervention, which ultimately may positively affect the patients overall function and independence. Several authors recommend interventions aimed at improving trunk control post stroke [13,14,[47][48][49][50][51], and this is also recommended in a recent systematic review [52].…”
Section: Clinical Relevancementioning
confidence: 99%